Qira’at dalam Tafsir Marah Labid: Studi Analisis Penggunaan dan Implikasi Qira’at atas Hukum - Moh. Fathurrozi (Universitas Islam Negeri Imam Bonjol Padang, 2023)
This article discusses the usage and implications of various qira'at (recitations) on istinbath al-hukm (deduction of legal rulings) in the tafsir